The killing stones [large type] - Cleeves, Ann (Cleeves, Ann. Detective Jimmy Perez novel., 2025)
"It's been several years since Detective Jimmy Perez left Shetland. He has settled into his new home in Orkney, the group of islands, off the northern coast of Scotland, with his partner Willow Reeve and their growing family. One stormy winter night, his oldest and closest friend, Archie Stout, goes missing. Ever the detective, Perez catches a boat to the island of Westray, where Archie worked as a farmer and lived with his wife and children. But when he arrives he finds a shocking Archie's body, on an archaeological dig site and an ancient Westray story stone with precise spirals carved into it beside him, the clear murder weapon. The artifact, taken from a nearby museum, seems to suggest a premediated murder. But Perez is so close to the case that he struggles to maintain an objective distance from the potential suspects. He finds it difficult to question Archie's wife, whom he's known for years. Rumors swirl about the dead man's relationship with a young woman new to the island, an artist. With each new lead, the case becomes more twisted and Perez wonders if he will ever find out what happened in his friend's final days"--